2005
DOI: 10.1111/j.1365-294x.2005.02598.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation implications of complex population structure: lessons from the loggerhead turtle (Caretta caretta)

Abstract: Complex population structure can result from either sex-biased gene flow or population overlap during migrations. Loggerhead turtles (Caretta caretta) have both traits, providing an instructive case history for wildlife management. Based on surveys of maternally inherited mtDNA, pelagic post-hatchlings show no population structure across the northern Atlantic (phi(ST) < 0.001, P = 0.919), subadults in coastal habitat show low structure among locations (phi(ST) = 0.01, P < 0.005), and nesting colonies along the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
196
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(217 citation statements)
references
References 103 publications
9
196
2
Order By: Relevance
“…While North Atlantic and Mediterranean loggerhead turtles are a relatively well-studied systems in population genetics and connectivity research Encalada et al 1998;Laurent et al 1998;Bowen et al 2004Bowen et al , 2005Carreras et al 2006Carreras et al , 2007Lee 2008), key gaps in sampling still remain. The second largest nesting aggregation of the globally endangered loggerhead sea turtle (IUCN 2007) in the Atlantic Ocean is found at the Cape Verde Islands, which is also the only major rookery in Western Africa for this species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While North Atlantic and Mediterranean loggerhead turtles are a relatively well-studied systems in population genetics and connectivity research Encalada et al 1998;Laurent et al 1998;Bowen et al 2004Bowen et al , 2005Carreras et al 2006Carreras et al , 2007Lee 2008), key gaps in sampling still remain. The second largest nesting aggregation of the globally endangered loggerhead sea turtle (IUCN 2007) in the Atlantic Ocean is found at the Cape Verde Islands, which is also the only major rookery in Western Africa for this species.…”
Section: Introductionmentioning
confidence: 99%
“…Samples from most major loggerhead turtle rookeries, albeit with significant exceptions such as the Cape Verde Islands, have been sequenced at the mitochondrial DNA control region Bowen et al 2005;Carreras et al 2007;Reis et al in press), revealing significant genetic differentiation among most rookeries. More recent control region research identified five rookery groups in the Western Atlantic (Bowen et al 2005). In the eastern Mediterranean, Carreras et al (2007) found four independent units, most of them characterized by one exclusive haplotype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As sea turtles approach maturity, they move to waters in closer proximity to nesting beaches (Bowen et al, 2005) and commence migratory breeding cycles every one to nine years depending on the species and ocean basin (Carr and Ogren, 1960;Miller, 1997). During nesting season, adult turtles temporarily reside in neritic waters along the continental shelf, just off nesting beaches (Stoneburner, 1982;Mortimer and Porter, 1989;TEWG, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Like the seals and birds described above, they are highly migratory, traveling great distances between reproductive sites and foraging grounds . While breeding areas are relatively discrete geographically and genetically, foraging areas for marine turtles may comprise individuals from multiple populations and geographic locations (Bowen et al 2005;Murphy et al 2006;Bolker et al 2007;Doyle et al 2008;López-Mendilaharsu et al 2009;Wallace et al 2010;Tucker et al 2014). Their broad distribution makes them vulnerable to a variety of anthropogenic threats including interactions with fishing gear (Stewart et al 2016), entanglement, and marine debris ingestion at varying spatial scales, which are important to understand for management purposes because certain populations (especially small ones) may be differentially affected by these threats (Stewart et al 2016).…”
mentioning
confidence: 99%